Affective responses to resistance exercise: Toward a consensus on the timing of assessments. (September 2022) - Andrade, A.J.; Ekkekakis, P.; Evmenenko, A.; Monteiro, D.; Rodrigues, F.; Cid, L.; Teixeira, D.S.
Abstract: Tailoring exercise prescriptions aimed at improving affective responses to resistance exercise may promote pleasurable experiences and thus exercise adherence. The purpose of this study was to evaluate different timing protocols for administering rating scales for the assessment of affective valence (Feeling Scale, FS) and perceived activation (Felt Arousal Scale, FAS) during resistance exercise. Thirty-three experienced male exercisers ( M = 36.42 ± 7.72 years) completed the FS and FAS at different times at three percentages of one-repetition maximum (%1RM) during two exercises (bench press, squat). No differences emerged among different assessment time points and %1RM. These findings suggest that the post-exercise "affective rebound" phenomenon found in aerobic exercise may not be as pronounced in resistance exercise. Therefore, the results support the use of FS and FAS in resistance exercise, administered immediately after a set, over a wide range of %1RM and exercises. Mounting evidence suggests that the use of these scales in resistance exercise could allow researchers and practitioners to evaluate affective responses that may be important for adherence. Highlights: Promoting pleasurable experiences in resistance exercise may promote adherence. Timing of affective assessments does matter in resistance exercise. Affective rebound may not be as pronounced as reported in aerobic exercise.